(3VHW ef ZHQ ajef bjOg GHf MLQs - (3jhSa Hf MSf Hf CMeO Hf MSf Hf YHO GdgGOj GdUGdMj, LeGd GdOjf, GHf GdeHQO,J (B909 (3g` s; (3TgGH GdOjf CHh GdaVd CMeO Hf Ydj Hf MLQ GdYSbdGfi,J (B852 (3g` s
(3ChdgG (B:s
(3Chdg GdOjHGLI (B: (3aEfi cfJ bO hVYJ cJGHkG ai JbjjO GdCSeGA , Ke GdWYJ Ydi cJGH GHf MLQ JbQjH GdJgPjH ajg JbjjO cKjQ , aCQOGJ Cf CPcQg ajg , aQCjJ Pdc jWhd Hg , aCaQOJg gfG hSejJg s
(3eQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B95 s
Keywords: (3GdJGQjNs